Diagnosis and Management of Asthma in Preschoolers: A Canadian Thoracic Society and Canadian Paediatric Society Position Paper - Francine M Ducharme; Sharon D Dell; Dhenuka Radhakrishnan; Roland M Grad; Wade TA Watson; Connie L Yang; Mitchell Zelman (Canadian Respiratory Journal)
Asthma often starts before six years of age. However, there remains uncertainty as to when and how a preschool-age child with symptoms suggestive of asthma can be diagnosed with this condition. This delays treatment and contributes to both short- and long-term morbidity. Members of the Canadian Thoracic Society Asthma Clinical Assembly partnered with the Canadian Paediatric Society to develop a joint working group with the mandate to develop a position paper on the diagnosis and management of asthma in preschoolers.